Inhibitory Effects of Momordicine I on High-Glucose-Induced Cell Proliferation and Collagen Synthesis in Rat Cardiac Fibroblasts. (8th October 2018) - Chen, Po-Yuan; Shih, Neng-Lang; Hao, Wen-Rui; Chen, Chun-Chao; Liu, Ju-Chi; Sung, Li-Chin
Abstract : Diabetes-associated cardiac fibrosis is a severe cardiovascular complication. Momordicine I, a bioactive triterpenoid isolated from bitter melon, has been demonstrated to have antidiabetic properties. This study investigated the effects of momordicine I on high-glucose-induced cardiac fibroblast activation. Rat cardiac fibroblasts were cultured in a high-glucose (25 mM) medium in the absence or presence of momordicine I, and the changes in collagen synthesis, transforming growth factor- β 1 (TGF- β 1) production, and related signaling molecules were assessed. Increased oxidative stress plays a critical role in the development of high-glucose-induced cardiac fibrosis; we further explored momordicine I's antioxidant activity and its effect on fibroblasts. Our data revealed that a high-glucose condition promoted fibroblast proliferation and collagen synthesis and these effects were abolished by momordicine I (0.3 and 1 μ M) pretreatment. Furthermore, the inhibitory effect of momordicine I on high-glucose-induced fibroblast activation may be associated with its activation of nuclear factor erythroid 2-related factor 2 (Nrf2) and the inhibition of reactive oxygen species formation, TGF- β 1 production, and Smad2/3 phosphorylation. The addition of brusatol (a selective inhibitor of Nrf2) or Nrf2 siRNA significantly abolished the inhibitory effect of momordicine I on fibroblast activation. Our findings revealed that the antifibrotic effect of momordicine I was mediated, at least partially, by the inhibition of the TGF- β 1/Smad pathway, fibroblast proliferation, and collagen synthesis through Nrf2 activation. Thus, this work provides crucial insights into the molecular pathways for the clinical application of momordicine I for treating diabetes-associated cardiac fibrosis.